The Prevalence of Positional Obstructive Sleep Apnoea in a Sample of the Saudi Population - Siraj O. Wali; Ibrahim AlQassas; Sultan Qanash; Hani Mufti; Malak Alamoudi; Maha Alnowaiser; Reem Bakraa; Abdullah Alharbi; Wejdan Ossra; Faris Alhejaili; Ranya Alshumrani; Ghadah A. Batawi (Springer, 2023)
Abstract Purpose Positional obstructive sleep apnoea (POSA) is of important clinical significance, as positional treatment can augment or obviate continuous positive airway pressure. This study aimed to determine the prevalence of POSA and its characteristics using different definitions. Methods We retrospectively examined a cohort of patients who underwent polysomnography (PSG) between 2013 and 2019 at two sleep centres. Demographic data and PSG data were collected from 624 patients with an apnoea-hypopnea index (AHI) ≥ 5. POSA was defined using different criteria as follows: (1) AHI of at least twice as high in the supine position as in the lateral position (Cartwright' s definition). (2) A supine AHI ≥ 10 and a lateral AHI < 10 (Marklun's definition). (3) AHI of at least twice as high in the supine position than in the lateral position, with the lateral AHI not exceeding 5 (Mador's definition or Exclusive POSA; e-POSA). (4) AHI ≥ 15/h; a supine AHI ≥ twice that of the nonsupine AHI ≥ 20 min of sleep in the supine and nonsupine positions; and a nonsupine AHI < 15 (Bignold's definition). Results The prevalence of POSA was 54% (Cartwright), 38.6% (Mador), 33.8% (Marklund) and 8.3% (Bignold). Multivariate regression analysis showed a body mass index (BMI) < 35 kg/m2 was the only significant predictor of POSA. Mador's definition had the highest diagnostic yield (sensitivity 63%; specificity 100%; area under the receiver operating characteristic curve 90.2%). Conclusion POSA is common, but its prevalence depends on the definition used. Low BMI was identified as a significant predictor.